PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP DAYA TAHAN ATLET SEPAK BOLA PADA CLUB BROSTER SAMUK KECAMATAN SIANTAN UTARA KABUPATEN KEPULAUAN ANAMBAS - Arfandi Arfandi; Ramadi Ramadi; Agus Prima Aspa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the stamina of the football players of Club Broster Samuk, North Siantan District, Anambas Islands Regency, which is still not optimal, many athletes at the 20th minute are tired and the movement is slow. was to determine the effect of circuit training on strength. The population in this research were all soccer athletes using a total sampling technique of 22 athletes. This type of research uses a one-group pre-test-post-test design, using the Bleep Test. Based on the data analysis and discussion described previously, the following conclusions can be drawn: There is an effect of circuit training on the endurance of football athletes in the Broster Samuk team, North Siantan District, Anambas Islands Regency. (8.27 > 1.721), then received H_а.Keywords: Circuit Trauning, Durability, Foot Ball